Evaluating First Aid Resources in Elementary Schools: a Case Study in the Upper North Region of Thailand - ปันสกุล , นัฐพล; ศรีสุขคำ, ทวีวรรณ; แก่นท้าว, ศุภกาญจน์; ผุดผ่อง , ปุณญิสา; นพวงศ์ , วิภาดา; คำหว่าง, เมธี (Journal of Health Science of Thailand, 2025)
Thailand’s schools are designed to provide students with access to basic healthcare services within the school premises. Therefore, this study aimed to examine the availability of first aid resources in elementary schools in the upper northern region of Thailand. A mix of quantitative and qualitative methods was employed. The data collection phase took place between June and September 2022, with a specific focus on schools within the designated region. The quantitative data were analyzed using descriptive statistics, while the qualitative data underwent thorough content analysis. The results indicated that the majority of the 62 elementary schools were of medium size (77.4%) and successfully passed the health promotion school gold assessment (93.1%). Each of the examined schools was equipped with a minimum of one designated teacher responsible for school health, while the maximum number of such teachers in any school was five. Most of the school health teachers had an educational background unrelated to health. Interestingly, a considerable number of these teachers had never received training in drug use and first aid. However, they still played a vital role in administering and dispensing medicines within the school setting. A majority of schools (53.2%) offered first aid rooms that were clearly separated from other areas. Nearly all schools had essential medical equipment such as a medicine cabinet, weighing machine, height gauge, and eye test strips. However, some schools still lacked certain supplies necessary for a fully equipped first aid room, such as bedspreads, blankets, and other items. The majority of schools had firstaid room diaries, but they lacked utilization of these first-aid room diaries. The study’s findings highlight that the scarcity of resources required for offering first aid services in schools remains a significant challenge. As a solution, it is crucial for relevant agencies to develop guidelines for allocating resources effectively, ensuring the provision of adequate and systematic health services.